(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2007)
Additional findings of fusulinids and corals from Permian rocks of Western Karakorum and Eastern Hindu Kush are reported. The Lashkargaz Fm. of Western Karakorum (Sakmarian - Kubergandian in age), is redefined in its uppermost part. A new unit of sucrosic dolostone, the Ini Sar Fm., of early Murgabian age in its basal part, is established for a level previously attributed to the Ailak Fm. The Ailak Fm. is confirmed to be Late Permian in its lower part. A rich fusulinid fauna of early Kubergandian age was found in a carbonate nappe previously unidentified, along the Pakistan-Afghanistan border in the Eastern Hindu Kush.